Getting Incentives Right: Improving Torts, Contracts, and Restitution - Robert D. Cooter, Ariel Porat (Princeton University Press, 2014)
Law should promote the wellbeing of people. Tort law, which deals with accidents, should reduce their cost and frequencyâ€”an important matter, as accidents cause approximately 42 million hospital visits and 182 thousand deaths per year in the United States.1 Contract law, called upon in a range of activities from renting an apartment to buying an oil field, should lubricate these transactions. Transactions based on contract law generate approximately fifteen trillion dollars of national income annually in the United States.2 Restitution law, which mostly discourages people from using what belongs to others without their consent, should encourage people to supply benefits for others that markets cannot provide. In the law of torts, contracts, or restitution, the plaintiff in a suit is usually a private legal person such as a citizen or corporation, not the state as in a criminal trial. The defendant is often a private legal person as well. For these reasons, the law of torts, contracts, and restitution is called private law. By explaining how private law reduces accident costs, lubricates bargains, and encourages unrequested benefits, we will show three ways to improve the law of torts, contracts, and restitution. Before presenting our main claims, however, we briefly summarize the received economic analysis of torts, contracts, and restitution. Tort law creates incentives for manufacturers to design safer products, injurers and victims to take precautions, insurance companies to adjust their coverage, governments to build safer roads, and so on. By imposing the cost of accidents on the parties who can best avoid them, tort law can reduce the cost of accidents to society. Unfortunately, when tort law or regulations fail to do so, much money, time, and effort spent on preventing accidents are wasted. Thus, investments in precaution are too high or too low when the negligent injurersâ€™ liability does not correspond to the social harm that injurers cause. Indeed, we spend too much money reducing a few small losses, as with some industrial chemicals, but we do not spend enough reducing numerous large losses, as with kerosene space heaters.3 A better use of the same resources could provide more safety at no more cost. â€œInefficient expendituresâ€ on safety sounds like dull accounting, but it is a matter of life and death. To make the world safer without wasting money, judges, legislators, and regulators need to improve tort law